Liquid crystal polymer film and manufacturing method thereof

KR103021384B1Active Publication Date: 2026-09-16KOLON INDUSTRIES INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020210162580
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-23
Publication Date
2026-09-16
Estimated Expiration
2041-11-23

Smart Images

  • Figure 112021135204451-PAT00002_ABST
    Figure 112021135204451-PAT00002_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a liquid crystal polymer film having low dielectric constant and dielectric loss tangent, while also improving surface uniformity by reducing blistering, and to a liquid crystal polymer film.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a liquid crystal polymer film and a method for manufacturing the same. Background Technology

[0003] Recently, wireless communication is shifting to high-frequency ranges to increase communication speeds. Since wireless communication in this high-frequency range involves high transmission losses, high-frequency circuit boards utilizing insulators with low dielectric constants and dielectric loss tangents are under development; insulators using liquid crystal polymer resins are being considered as a representative example.

[0004] However, as the manufacturing process of electronic components such as high-frequency circuit boards is carried out at high temperatures, blisters occur, which are a phenomenon in which fine swelling occurs on the surface of liquid crystal polymer molded products during high-temperature processes.

[0005] Blisters that occur on the surface of such liquid crystal polymer films can cause defects, such as the formation of holes, during the manufacturing process of metal laminates or circuit boards.

[0006] To prevent blistering of liquid crystal polymer molded articles, there are methods such as using a composite resin composition containing a fibrous filler in the liquid crystal polymer and using a liquid crystal polymer composition containing glass fibers in the liquid crystal polymer, but the above methods produce molded articles based on a liquid crystal polymer composition containing additional materials rather than a single composition of liquid crystal polymer.

[0007] Therefore, there is a need to develop a new method for manufacturing liquid crystal polymer films that improves blister formation while maintaining low dielectric constant and dielectric loss tangent even when using a single liquid crystal polymer material. The problem to be solved

[0009] The present invention aims to provide a method for manufacturing a liquid crystal polymer film with low dielectric constant and dielectric loss tangent, and a liquid crystal polymer film with excellent surface uniformity by improving blistering. means of solving the problem

[0011] Hereinafter, a method for manufacturing a liquid crystal polymer film and a liquid crystal polymer film according to an embodiment of the present invention will be described.

[0013] Unless otherwise defined in this specification, all technical and scientific terms have the same meaning as generally understood by those skilled in the art to which the invention pertains. The terms used in the description of the invention are merely for the purpose of effectively describing specific embodiments and are not intended to limit the invention.

[0014] The singular forms used in this specification include plural forms unless the phrases clearly indicate otherwise.

[0015] As used in this specification, the meaning of 'includes' specifies certain characteristics, regions, integers, steps, actions, elements, and / or components, and does not exclude the existence or addition of other specific characteristics, regions, integers, steps, actions, elements, components, and / or groups.

[0016] The present invention is capable of various modifications and may take various forms, and specific embodiments are illustrated and described in detail below. However, this is not intended to limit the invention to the specific disclosed forms, and it should be understood that the invention includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the invention.

[0017] In this specification, where the positional relationship between two parts is described, for example, using expressions such as 'on', 'on the upper part', 'on the lower part', 'next to', etc., one or more other parts may be located between the two parts unless expressions such as 'immediately' or 'directly' are used.

[0018] In this specification, when temporal sequences are described, for example, using expressions such as ‘after,’ ‘following,’ ‘next,’ or ‘before,’ cases that are not continuous may be included unless expressions such as ‘immediately’ or ‘directly’ are used.

[0019] In this specification, the term 'at least one' should be understood to include all combinations that can be presented from one or more related items.

[0021] According to one embodiment of the invention, a method for manufacturing a liquid crystal polymer film is provided, comprising the steps of: melting a liquid crystal polymer composition including a liquid crystal polymer resin; and extruding the melted liquid crystal polymer composition using an extruder, wherein the temperature of the extruder satisfies a melt viscosity gradient (Poise / min) over time of the liquid crystal polymer resin being 5 or less.

[0022] As a result of continuous research on a method for manufacturing a liquid crystal polymer film, the inventors observed the change in the melting viscosity gradient of the liquid crystal polymer resin over time and confirmed that when the temperature satisfying the melting viscosity gradient (Poise / min) of the liquid crystal polymer resin over time being 5 or less is set as the temperature of the extruder to manufacture the liquid crystal polymer film, the occurrence of blisters is suppressed, the uniformity of the film surface is excellent, and the dielectric constant and dielectric loss tangent of the film are also low, resulting in excellent insulation properties, and thus completed the invention.

[0023] First, the inventors have determined that blisters occurring on the surface of a liquid crystal polymer film are related to the porosity inside the film. When voids are created inside the film during the manufacture of a liquid crystal polymer film, the air inside the voids expands as the voids are exposed to a high-temperature process, causing blisters to occur such as uneven film surfaces or the formation of holes.

[0024] Accordingly, research was conducted on temperature settings to minimize the formation of voids within the film during the manufacture of a liquid crystal polymer film, and it was discovered that the voids generated in the film are related to the temperature of the extruder during the process of extruding the liquid crystal polymer composition after melting it.

[0025] Specifically, by observing the change in the melt viscosity gradient of the liquid crystal polymer resin over time, it was confirmed that when a liquid crystal polymer film is manufactured by setting the temperature of the extruder to satisfy a melt viscosity gradient (Poise / min) of the liquid crystal polymer resin over time of 5 or less, the occurrence of micropores inside the film is suppressed, thereby preventing blisters from forming on the surface of the liquid crystal polymer film.

[0026] The meaning that the melt viscosity gradient (Poise / min) of the above liquid crystal polymer resin over time satisfies 5 or less means that the rate of increase in melt viscosity over time is reduced, and the fluidity of the molten liquid crystal polymer composition is increased.

[0027] Unlike conventional thermoplastic resins, liquid crystal polymer resins tend to exhibit an increase in melt viscosity even in the molten state at specific temperatures. This is understood to be because, unlike conventional crystalline thermoplastic resins where crystals melt at the melting temperature, liquid crystal polymer resins continue to grow even in the molten state up to a specific temperature. This increase in melt viscosity over time implies that it becomes difficult to remove air bubbles generated within the resin due to air introduced during movement inside the extruder, voids in the resin pellets, and voids between pellets.

[0028] Accordingly, when the process temperature of the extruder is set to a high rate of increase in the melting viscosity of the liquid crystal polymer resin, voids are generated inside the film and blisters are generated on the surface of the liquid crystal polymer film. However, when the process temperature of the extruder is set to a low rate of increase in the melting viscosity of the liquid crystal polymer resin, specifically a temperature where the gradient of the melting viscosity of the liquid crystal polymer resin over time (Poise / min) is 5 or less, the fluidity of the molten liquid crystal polymer composition is improved, and the generation of bubbles in the molten material is reduced. Consequently, the generation of voids inside the film is suppressed, and the formation of blisters on the surface of the liquid crystal polymer film is reduced, thereby increasing the uniformity of the film surface.

[0029] In addition, when manufacturing a liquid crystal polymer film using the above method for manufacturing a liquid crystal polymer film, a film that does not blister can be produced using a single liquid crystal polymer resin material without adding additional materials such as fillers, and a uniform film surface can also be obtained.

[0030] Meanwhile, the fact that the melt viscosity gradient (Poise / min) of the liquid crystal polymer resin over time satisfies 5 or less means that the temperature of the extruder satisfies the following mathematical formula 1.

[0031] [Mathematical Formula 1]

[0032] [(Melting viscosity of liquid crystal polymer resin after n minutes) - (Melting viscosity of liquid crystal polymer resin at the beginning)] / n minutes ≤ 5 (Poise / min)

[0034] For example, if the melt viscosity is measured at 3-minute intervals, and the initial melt viscosity (after 3 minutes) at the temperature to be measured (evaluation temperature) is 383 Poise and the melt viscosity after 12 minutes (i.e., after 15 minutes) is 395 Poise, the melt viscosity slope calculated by the above mathematical formula 1 is 1 (Poise / min).

[0035] [Mathematical Formula 1]

[0036] [(395 Poise)-(383 Poise)] / 12 min = 1 (Poise / min)

[0038] The melt viscosity gradient of such liquid crystal polymer resins can be determined by the change in melt viscosity according to the residence time of the liquid crystal polymer resin at different temperatures using a capillary rheometer. Specific melt viscosity measurement methods are described in the experimental examples below.

[0039] As described above, a small value of the melt viscosity gradient over time of the liquid crystal polymer resin means that the rate of increase in melt viscosity over time is reduced, and thus the fluidity of the molten liquid crystal polymer composition is increased. Therefore, as the melt viscosity gradient (Poise / min) over time of the liquid crystal polymer resin is 5 or less, 4 or less, 3 or less, 2 or less, or 1 or less, the phenomenon of void formation inside the film can be improved, and accordingly, the occurrence of blisters can be reduced and the uniformity of the surface can be increased.

[0040] Meanwhile, as a result of measuring and confirming the temperature satisfying the melt viscosity gradient (Poise / min) of the liquid crystal polymer resin over time being 5 or less, it was confirmed that the temperature satisfying the melt viscosity gradient (Poise / min) being 5 or less is 25°C or more and 27°C or more higher than the melting temperature of the liquid crystal polymer resin.

[0041] That is, when the molten liquid crystal polymer resin exceeds a certain temperature, the slope of the melting viscosity of the liquid crystal polymer resin over time becomes 5 or less, and thereafter, as the temperature continues to increase, the change in the slope of the melting viscosity approaches 0.

[0042] The melting temperature of such liquid crystal polymer resins can be confirmed by Differential Scanning Calorimetry (DSC). Specific methods for measuring the melting temperature are described in the experimental examples below.

[0044] Meanwhile, the method for manufacturing a liquid crystal polymer according to the above embodiment comprises the steps of: melting a liquid crystal polymer composition containing a liquid crystal polymer resin; and extruding the molten liquid crystal polymer composition using an extruder. Generally, a liquid crystal polymer film can be obtained by melting and kneading a liquid crystal polymer composition containing a thermoplastic liquid crystal polymer resin using an extruder and extruding the molten composition through a slit of a die. Generally, a T-shaped die or a circular die may be used as the die.

[0045] At this time, the temperature of the extruder is set to a temperature that satisfies the condition that the melt viscosity gradient (Poise / min) of the liquid crystal polymer resin over time is 5 or less, as described above.

[0046] Meanwhile, the extruded liquid crystal polymer film can be stretched as needed. Stretching methods may include uniaxial stretching, biaxial stretching, inflation, laminate stacking stretching, etc.

[0047] In addition, a laminate can be formed by bonding another thermoplastic polymer film simultaneously with the formation of the liquid crystal polymer film at the die slit. That is, a co-extruded film in which a liquid crystal polymer layer and another thermoplastic polymer layer are laminated can be produced using a plurality of extruders and dies. The other thermoplastic polymer may be a polyolefin such as polyethylene, polypropylene, or ethylene-α-olefin copolymer; a polystyrene; a polycarbonate; a polyester such as polyethylene terephthalate or polybutylene terephthalate; a polyacetal; a polyamide; a polyphenylene ether; a polyethersulfone; an ethylene-vinyl acetate copolymer; a polyvinyl chloride; a polyvinylidene chloride; a polyphenylene sulfide; a fluoropolymer, etc.

[0048] In addition, the liquid crystal polymer film may be subjected to surface treatment to improve other physical properties depending on the required purpose. For example, this may include plasma surface treatment, corona discharge surface treatment, deposition, sputtering, solvent immersion treatment, etc.

[0049] Meanwhile, the liquid crystal polymer resin included in the liquid crystal polymer composition according to the above embodiment may be a liquid crystal polymer capable of melt molding (or a polymer capable of forming an optically anisotropic molten phase), and the thermoplastic liquid crystal polymer may be a liquid crystal polymer capable of melt molding, and although its chemical composition is not particularly limited, for example, a thermoplastic liquid crystal polyester, or a thermoplastic liquid crystal polyesteramide in which an amide bond is introduced therein.

[0050] In addition, the liquid crystal polymer resin may be a polymer in which isocyanate-derived bonds, such as imide bonds, carbonate bonds, carbodiimide bonds, or isocyanurate bonds, are additionally introduced to an aromatic polyester or aromatic polyesteramide.

[0051] For example, the thermoplastic liquid crystal polyester may be prepared primarily from aromatic hydroxycarboxylic acids, aromatic dihydroxy, aromatic dicarboxylic acids, aromatic diamines, aromatic hydroxyamines and / or aromatic aminocarboxylic acid monomers.

[0052] The above aromatic hydroxycarboxylic acid monomers are not limited thereto, but may be, for example, 2-hydroxybenzoic acid, 3-hydroxybenzoic acid, 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 5-hydroxy-2-naphthoic acid, 3-hydroxy-2-naphthoic acid, 4-(4-hydroxyphenyl)benzoic acid or 4-(3-hydroxyphenyl)benzoic acid.

[0053] The above aromatic dihydroxy monomers are not limited thereto, but may be, for example, 1,4-dihydroxybenzene, 1,3-dihydroxybenzene, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-naphthalene dicarboxylic acid, 1,6-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 4,4'-dihydroxybiphenyl or 4,4'-dihydroxybiphenyl ether, etc.

[0054] The above aromatic dicarboxylic acid monomer is not limited thereto, but may be, for example, terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, biphenyl-4,4'-dicarboxylic acid or 4,4'-dicarboxydiphenyl ether, etc.

[0055] The monomer of the above aromatic diamine monomer is not limited thereto, but may be, for example, 1,4-diaminobenzene, 1,3-diaminobenzene, 1,5-diaminonaphthalene or 1,8-diaminonaphthalene.

[0056] The above aromatic hydroxyamine monomers are not limited thereto, but may be, for example, 4-aminophenol, 3-aminophenol, 4-amino-1-naphthol, 5-amino-1-naphthol, 6-amino-2-naphthol, or 4-amino-4'-hydroxybiphenyl, etc.

[0057] The above aromatic aminocarboxylic acid monomer is not limited thereto, but may be, for example, 4-aminobenzoic acid, 3-aminobenzoic acid, or 6-amino-2-naphthoic acid.

[0058] The above thermoplastic liquid crystal polyester is not limited thereto, but may be, for example, Type I composed of 4-hydroxybenzoic acid, terephthalic acid, and 4,4'-dihydroxybiphenyl, Type II composed of 4-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, and Type III composed of 4-hydroxybenzoic acid, terephthalic acid, and ethylene glycol.

[0059] In addition, representative commercial products currently on the market include Type I, Sumitomo Chemical’s Sumika Super and Solvay’s Zydar; Type II, Celanese’s Vectra; and Type III, Unitica’s Rodrun or Mitsubishi Engineering Plastics’ Novaculate.

[0061] According to another embodiment of the invention, a liquid crystal polymer film is provided, comprising a liquid crystal polymer resin, wherein the porosity inside the film is less than 1%.

[0062] As described above, when a liquid crystal polymer film is manufactured by observing the change in the melt viscosity gradient of the liquid crystal polymer resin over time and setting the temperature of the extruder to satisfy a melt viscosity gradient (Poise / min) of 5 or less over time, the occurrence of fine pores inside the film is suppressed, and the liquid crystal polymer film manufactured accordingly can have a porosity of less than 1%, less than 0.7%, or less than 0.5%.

[0063] As the porosity of the liquid crystal polymer film is less than 1%, the occurrence of blisters is suppressed, and the film surface can have excellent uniformity.

[0064] The porosity of such liquid crystal polymer films can be calculated based on the apparent density and true density of the film, and the apparent density can be obtained using an electronic hydrometer (Alpha Mirage, MD-300S). A specific method for measuring porosity is described in the experimental examples below.

[0065] Meanwhile, the liquid crystal polymer film may have an apparent density of 1.386 g / cm³ or 1.393 g / cm³ according to ASTM D792. As the apparent density of the liquid crystal polymer film increases, the porosity of the liquid crystal polymer film decreases, and as the apparent density of the film according to ASTM D792 exceeds 1.386 g / cm³, the occurrence of blisters is suppressed, and the film surface can have excellent uniformity.

[0066] Meanwhile, the above liquid crystal polymer resin is as described above, and at a temperature 25°C or higher and 27°C or higher than the melting temperature of the liquid crystal polymer resin, the gradient of melt viscosity over time (Poise / min) of the liquid crystal polymer resin may be 5 or less.

[0067] Meanwhile, the liquid crystal polymer film according to the other embodiment above may have an arithmetic mean illuminance of at least one surface of 500 nm or less, 450 nm or less, or 400 nm or less. Such arithmetic mean illuminance can be measured using a 3D Optical Profiler (Bruker, NPFLEX). A specific method for measuring arithmetic mean illuminance is described in the experimental examples below.

[0068] In addition, the thickness of the liquid crystal polymer film may be 10 μm or more, 20 μm or more, 30 μm or more, or 1000 μm or less, 900 μm or less, or 800 μm or less.

[0069] In addition, the liquid crystal polymer film may have a dielectric constant measured in a microwave molecular orientation system of 0.1 or more, 0.2 or more, 0.3 or more, or 5.0 or less, 4.0 or less, or 3.5 or less.

[0070] In addition, the liquid crystal polymer film may have a dielectric loss tangent measured in a microwave molecular orientation system of 0.010 or less, 0.005 or less, or 0.003 or less.

[0071] Meanwhile, the liquid crystal polymer resin may be a thermoplastic liquid crystal polyester, and the details regarding the thermoplastic liquid crystal polyester are as described above.

[0073] A liquid crystal polymer film according to the other embodiment above may be applied to a circuit board. For example, the circuit board may include the liquid crystal polymer film and a conductive circuit layer formed on one surface of the liquid crystal polymer film.

[0074] The formation of the above-mentioned conductive circuit can be carried out according to known methods, for example, (a) a method of forming a conductive circuit by laminating a liquid crystal polymer film and a metal layer by thermal compression and then performing an etching treatment, etc., and (b) a method of forming a conductive layer on the surface of a liquid crystal polymer film by a vapor phase method such as sputtering, ion plating, or vacuum deposition, or by a wet plating method to form a conductive circuit.

[0075] The above circuit board may be a single-layer circuit board having a single metal layer (or conductive circuit layer), but in order to satisfy the requirement for high functionality of the circuit board, it may be a multi-layer circuit board having a plurality of metal layers (or conductive pattern layers) (e.g., a two-layer circuit board, a three-layer circuit board, a four-layer circuit board, etc.). In this case, in the circuit board, the patterned metal layer may be used as a signal line or ground plane line of a predetermined pattern as needed.

[0076] Since the above circuit board has a stable dielectric constant before and after heating even in the high-frequency region, and the above liquid crystal polymer film also has low dielectric properties, it can be used as a high-frequency circuit board. The high-frequency circuit board may not only consist of a circuit that simply transmits high-frequency signals, but may also include a circuit in which a transmission path that transmits signals other than high-frequency signals is installed on the same plane, such as a transmission path that converts a high-frequency signal into a low-frequency signal and outputs the generated low-frequency signal externally, or a transmission path for supplying power for driving high-frequency compatible components.

[0077] Examples of such transmission lines include various known or commonly used transmission lines, such as coaxial lines, strip lines, microstrip lines, coplanar lines, and parallel lines. Effects of the invention

[0079] According to the present invention, a method for manufacturing a liquid crystal polymer film with low dielectric constant and dielectric loss tangent, and a liquid crystal polymer film with excellent surface uniformity by improving blistering, can be provided. Brief explanation of the drawing

[0081] Figure 1 is a photograph showing the surface appearance of the liquid crystal polymer film of Example 1. Figure 2 is a photograph of the surface appearance of the liquid crystal polymer film of Comparative Example 1. Specific details for implementing the invention

[0082] Preferred embodiments are presented below to aid in understanding the invention. However, the following embodiments are merely illustrative of the invention and do not limit the invention to these embodiments.

[0084] <Experimental Example>

[0085] 1. Measurement of melt viscosity of liquid crystal polymer resin

[0086] The slope of the change in melt viscosity (Poise / min) according to the residence time of the liquid crystal polymer resin at different temperatures was determined using a capillary rheometer. The capillary rheometer had a length of 20 mm and a diameter of 1 mm, with a piston diameter of 12 mm, and the melt viscosity was measured at 3-minute intervals for 15 minutes at a shear rate of 500 / sec.

[0087] The slope of the melt viscosity of the liquid crystal polymer resin over time for each temperature was calculated and is shown in Table 1 below.

[0089] 2. Measurement of melting temperature

[0090] The melting temperature of the liquid crystal polymer resin was determined by Differential Scanning Calorimetry (DSC). Using a Q20 from TA Instruments, the resin was completely melted at a heating rate of 5°C / min, then the molten resin was rapidly cooled to -10°C at a rate of 50°C / min, and the temperature at the point where the endothermic peak appeared while heating again at 5°C / min was set as the melting temperature of the film. The melting temperatures of the evaluated resins are shown in Table 1 below.

[0092] profit Resin melting temperature (°C) Evaluation temperature (°C) Hourly viscosity (Poise) Viscosity change gradient (Poise / min) 3 minutes 6 minutes 9 minutes 12 minutes 15 minutes Reference Example 1 LCP A 283 295 677 774 853 883 958 23 Reference Example 2 LCP A 283 305 478 517 545 562 584 9 Reference Example 3 LCP A 283 310 383 390 388 393 395 1 Reference Example 4 LCP A 283 320 313 306 313 321 321 1 Reference Example 5 LCP A 283 340 224 224 221 224 224 0 Reference Example 6 LCP B 282 295 724 791 856 1,013 1,030 26 Reference Example 7 LCP B 282 305 527 558 587 635 646 10 Reference Example 8 LCP B 282 310 430 435 445 435 433 0 Reference Example 9 LCP B 282 320 378 375 373 368 378 0 Reference Example 10 LCP B 282 340 274 272 274 274 273 0

[0093] - LCP A: CX-2199 manufactured by ENEOS Liquid Crystal Co., Ltd. - LCP B: Vectra A950 manufactured by Celanese

[0095] <Examples and Comparative Examples: Preparation of Liquid Crystal Polymer Films>

[0096] Example 1

[0097] A film was produced using a thermoplastic liquid crystal polyester pellet (CX-2199) manufactured by ENEOS Liquid Crystal Co., Ltd. and a uniaxial extruder (Labtech, LE30-30 / CV). The extruder's L / D ratio was 30 and its diameter was 30 mm. A T-die was used, with a die slit spacing of 0.5 mm and a slit width of 300 mm. Additionally, the extruder temperature was set to 340°C, the die temperature to 295°C, and the screw speed to 60 rpm to produce a film with a thickness of 50 μm.

[0099] Examples 2 to 6

[0100] The same thermoplastic liquid crystal polyester pellets (CX-2199 manufactured by ENEOS Liquid Crystal Co., Ltd.) as in Example 1 were used with the same extruder as in Example 1, and films were produced by varying the extruder temperature and screw speed as shown in Table 2.

[0102] Examples 7 to 12

[0103] The same extruder as in Example 1 was used with thermoplastic liquid crystal polyester pellets (Vectra A950) manufactured by Celanese, and films were produced by varying the extruder temperature and screw speed as shown in Table 3.

[0105] Comparative Example 1

[0106] The same thermoplastic liquid crystal polyester pellets (CX-2199 manufactured by ENEOS Liquid Crystal Co., Ltd.) as in Example 1 were used with the same extruder as in Example 1. The extruder temperature was set to 295°C, the die temperature to 295°C, and the screw speed to 60 rpm to produce a film with a thickness of 50 μm.

[0108] Comparative Examples 2 to 4

[0109] Films were produced using the same extruder as in Example 1, but with different thermoplastic liquid crystal polyester, extruder temperature, and screw speed as shown in Table 4.

[0111] <Test Example>

[0112] 1. Measurement of film apparent density and porosity

[0113] The apparent density of the film according to ASTM D792 utilizes Archimedes' principle and is determined by the specific gravity based on the relationship between the mass of the film in air and the mass of the film when immersed in a solvent. The apparent density of the film was determined using an electronic hydrometer (Alpha Mirage, MD-300S), distilled water was used as the solvent for measurement, and the apparent density was calculated from a sample mass of 8g or more. The porosity of the film was calculated using the following Equation 2 based on the apparent density and true density of the film.

[0114] [Mathematical Formula 2]

[0115]

[0116] (Here, ρ1 is the true density of the liquid crystal polymer resin, which is 1.4 g / cm³, and ρ2 is the apparent density of the fabricated film. Also, ρa is the density of air at 1 atmosphere (0.0012 g / cm³).)

[0118] 2. Measurement of Dielectric Constant and Dielectric Loss Tangent

[0119] The dielectric constant and dielectric loss tangent of the liquid crystal polymer films of the examples and comparative examples were measured using a microwave molecular orientation analyzer (MOA-7015, OZ Scientific Instruments), and the results are shown in Tables 2 to 4 below. At this time, measurements were taken at a frequency of 15 GHz.

[0121] 3. Surface roughness measurement

[0122] The surface roughness of the liquid crystal polymer films of the examples and comparative examples was measured using a 3D Optical Profiler (Bruker, NPFLEX) to determine the arithmetic mean surface roughness. Specifically, in vertical scanning interferometry (VSI) mode, the microscope magnification was set to 2.5 to measure a surface image with dimensions of 4000 μm vertically and 4000 μm horizontally, and then the arithmetic mean surface roughness was calculated with a cut-off of 800 μm. The results are shown in Tables 2 to 4 below.

[0124] 4. Film Surface Evaluation

[0125] The liquid crystal polymer films of the examples and comparative examples were cut into a width of 20 mm x a length of 20 mm, inserted between two slide glass sheets (width 76 mm x length 26 mm x thickness 1 mm), and laminated using a hot press. During hot press lamination, the press pressure was 1 MPa and the hot press temperature was 260°C.

[0126] After hot press lamination, the film surface was visually observed using a stereomicroscope (Olympus SZX16, transmission mode, objective lens x2). The evaluation criteria are as follows, and the results are shown in Tables 2 to 4 below.

[0127] Meanwhile, FIG. 1 is a photograph of the surface appearance of the film of Example 1, and FIG. 2 is a photograph of the surface appearance of the film of Comparative Example 1.

[0128] <Evaluation Criteria>

[0129] - Good: No blisters, such as bulging or holes, formed on the film surface

[0130] - Defect: The film surface is bulging or blisters such as holes are formed

[0132] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Applicable resin LCP A LCP A LCP A LCP A LCP A LCP A Extruder temperature (°C) 340 330 320 310 340 320 Die temperature (°C) 295 295 295 295 295 295 Screw speed (rpm) 60 60 60 60 120 120 Film thickness (㎛) 50 50 50 50 100 100 Film apparent density (g / cm³) 1.397 1.399 1.397 1.395 1.397 1.397 Film porosity (%) 0.2 0.1 0.2 0.4 0.2 0.2 genetic constant 3.41 3.40 3.42 3.40 3.42 3.44 hereditary jeopardy 0.001 0.001 0.001 0.001 0.002 0.002 Surface roughness (nm) 320 317 363 379 257 279 Surface blister Good Good Good Good Good Good

[0133] Example 7 Example 8 Example 9 Example 10 Example 11 Example 12 Applicable resin LCP B LCP B LCP B LCP B LCP B LCP B Extruder temperature (°C) 340 330 320 310 340 320 Die temperature (°C) 295 295 295 295 295 295 Screw speed (rpm) 60 60 60 60 120 120 Film thickness (㎛) 50 50 50 50 100 100 Film apparent density (g / cm³) 1.397 1.397 1.397 1.394 1.397 1.397 Film porosity (%) 0.2 0.2 0.2 0.4 0.2 0.2 genetic constant 3.39 3.38 3.41 3.40 3.41 3.40 hereditary jeopardy 0.001 0.001 0.001 0.001 0.002 0.002 Surface roughness (nm) 303 320 306 321 269 274 Surface blister Good Good Good Good Good Good

[0134] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Applicable resin LCP A LCP A LCP B LCP B Extruder temperature (°C) 295 305 295 305 Die temperature (°C) 295 295 295 295 Screw speed (rpm) 60 60 60 60 Film thickness (㎛) 50 50 50 50 Film apparent density (g / cm³) 1.323 1.383 1.336 1.386 Film porosity (%) 5.5 1.2 4.6 1 genetic constant 3.37 3.39 3.38 3.40 hereditary jeopardy 0.001 0.001 0.001 0.001 Surface roughness (nm) 1746 481 987 537 Surface blister error error error error

[0135] - LCP A: CX-2199 manufactured by ENEOS Liquid Crystal Co., Ltd. - LCP B: Vectra A950 manufactured by Celanese

[0137] Referring to Tables 2 to 4 above, it was confirmed that the liquid crystal polymer film of the example has a porosity of less than 1% and does not produce blisters on the film surface, whereas the liquid crystal polymer film of the comparative example has a porosity of 1% or more and produces blisters on the film surface. This is believed to be because when the pores inside the film are exposed to high temperatures, the air within the pores expands, causing the film surface to bulge or form holes.

[0138] In addition, it was confirmed that when a film is produced by setting the extruder temperature to satisfy a melting viscosity gradient (Poise / min) of the liquid crystal polymer resin over time of 5 or less, as in the example, the porosity of the film is less than 1%, and when the extruder temperature is set to satisfy a melting viscosity gradient (Poise / min) of the liquid crystal polymer resin over time of 5 or more, as in the comparative example, the porosity of the film is 1% or more.

[0139] In addition, for films produced at a temperature where the melt viscosity gradient (Poise / min) is 5 or less, the surface roughness is also low, and it was confirmed that the film surface is uniform.

[0140] Meanwhile, in the evaluation of the melt viscosity of the reference example in Table 1, it was observed that although the evaluation temperature was higher than the melting temperature of the resin, the slope of the melt viscosity according to the residence time increased as the evaluation temperature decreased. This is believed to be because, unlike general crystalline resin-based thermoplastic resins where crystals melt at the melting temperature, liquid crystal polymer resins grow crystals even in the molten state up to a certain temperature, causing the melt viscosity to increase.

[0141] It is believed that the increase in melt viscosity over time makes it difficult to remove air introduced during the movement of the liquid crystal polymer resin inside the extruder, as well as bubbles in the voids of the pellet resin and between pellets, resulting in a higher porosity of the film. However, at temperatures where the gradient of melt viscosity with respect to residence time does not increase, crystals of the liquid crystal polymer resin are removed inside the extruder, improving the fluidity of the molten material and preventing the generation of bubbles within the molten material, which is believed to result in a lower porosity of the film.

Claims

Claim 1 A method for manufacturing a liquid crystal polymer film, comprising: a step of melting a liquid crystal polymer composition including a liquid crystal polymer resin; and a step of extruding the melted liquid crystal polymer composition using an extruder; wherein the temperature of the extruder satisfies a melt viscosity gradient (Poise / min) over time of the liquid crystal polymer resin being 5 or less. Claim 2 A method for manufacturing a liquid crystal polymer film according to claim 1, wherein the temperature of the extruder satisfies the following mathematical formula 1: [Mathematical Formula 1][(melt viscosity of liquid crystal polymer resin after n minutes)-(melt viscosity of initial liquid crystal polymer resin)] / n minutes ≤ 5 (Poise / min). Claim 3 A method for manufacturing a liquid crystal polymer film according to claim 1, wherein the temperature at which the melt viscosity gradient (Poise / min) of the liquid crystal polymer resin over time satisfies 1 or less is the temperature of the extruder. Claim 4 A method for manufacturing a liquid crystal polymer film according to claim 1, wherein the temperature of the extruder is at least 25°C higher than the melting temperature of the liquid crystal polymer resin. Claim 5 A method for manufacturing a liquid crystal polymer film, wherein, in claim 1, the liquid crystal polymer resin is a thermoplastic liquid crystal polyester. Claim 6 A liquid crystal polymer film comprising a liquid crystal polymer resin, wherein the porosity inside the film is less than 1%, and the gradient of the melt viscosity over time (Poise / min) of the liquid crystal polymer resin at a temperature 25°C or higher than the melting temperature of the liquid crystal polymer resin is 5 or less. Claim 7 In claim 6, a liquid crystal polymer film having an internal porosity of less than 0.5%. Claim 8 In claim 6, the film is a liquid crystal polymer film having an apparent density of more than 1.386 g / cm³ according to ASTM D792. Claim 9 In claim 6, the film is a liquid crystal polymer film having an apparent density of more than 1.393 g / cm³ according to ASTM D792. Claim 10 delete Claim 11 A liquid crystal polymer film according to claim 6, wherein the arithmetic mean roughness of at least one surface of the liquid crystal polymer film is 500 nm or less. Claim 12 In claim 6, the liquid crystal polymer film has a thickness of 10 to 1000 μm. Claim 13 In claim 6, the liquid crystal polymer resin is a thermoplastic liquid crystal polyester, and the liquid crystal polymer film.

Citation Information

Patent Citations

  • White reflection film for light-emitting diode element mount board, light-emitting diode element mount board arranged by use of white reflection film for light-emitting diode element mount board, and luminaire arranged by use of light-emitting diode element mount board

    JP2016157770A

  • White polyester film and reflective sheet

    KR1020090108595A

  • Reflective film, as well as liquid crystal display device, illumination device, and decorative product provided with same

    KR1020170135948A